2014
DOI: 10.1021/jm500853v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure–Activity Relationship Studies, and Antibacterial Evaluation of 4-Chromanones and Chalcones, as Well as Olympicin A and Derivatives

Abstract: On the basis of recently reported abyssinone II and olympicin A, a series of chemically modified flavonoid phytochemicals were synthesized and evaluated against Mycobacterium tuberculosis and a panel of Gram-positive and -negative bacterial pathogens. Some of the synthesized compounds exhibited good antibacterial activities against Gram-positive pathogens including methicillin resistant Staphylococcus aureus with minimum inhibitory concentration as low as 0.39 μg/mL. SAR analysis revealed that the 2-hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 77 publications
4
56
0
Order By: Relevance
“…aureus , compared than the reference drug chloramphenicol (Khan, Asiri, & Elroby, ). Evaluation of the antibacterial activity of modified structures of olympicin A from Hypericum olympicum showed that ( E )‐3‐(2‐(allyloxy) phenyl)‐1‐(2,4,6‐trihydroxyphenyl)prop‐2‐en‐1‐one ( 148 ) had a good activity against MRSA with MIC value of 0.39 μg/ml (Feng et al, ). Between the synthetic tricyclic flavonoids, compounds 149 and 150 (1,3‐dithiolium derivative) showed good activity with MICs of 0.25 and 1 μg/ml against S .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
“…aureus , compared than the reference drug chloramphenicol (Khan, Asiri, & Elroby, ). Evaluation of the antibacterial activity of modified structures of olympicin A from Hypericum olympicum showed that ( E )‐3‐(2‐(allyloxy) phenyl)‐1‐(2,4,6‐trihydroxyphenyl)prop‐2‐en‐1‐one ( 148 ) had a good activity against MRSA with MIC value of 0.39 μg/ml (Feng et al, ). Between the synthetic tricyclic flavonoids, compounds 149 and 150 (1,3‐dithiolium derivative) showed good activity with MICs of 0.25 and 1 μg/ml against S .…”
Section: Synthetic Derivatives Of Flavonoidsmentioning
confidence: 99%
“…In our ongoing efforts to discover new topoisomerase I inhibitors as antibacterial agents and to probe the topoisomerase I recognition [8, 9], we identified during high-throughput screening (HTS) assay development a compound NSC648059 ( 1 , Fig. 1) with low micromolar inhibitory activity (IC 50 = 0.8–2.0 µM) against Escherichia coli topoisomerase I.…”
Section: Introductionmentioning
confidence: 99%
“…One such pharmacophoric unit is chromone which is recognized as a useful motif for the design of biologically relevant entities and is also prevalent in many natural products. [5][6][7][8][9][10] Spiro chromanones too are known to be bio-active molecules with activities ranging from anti-inammatory, anti-cancer, anti-bacterial and anti-fungal properties.…”
Section: Introductionmentioning
confidence: 99%